Evaluate (2a

^{2}b

^{3}c

^{4} - 6x

^{3}y

^{4}z

^{5})

^{5}We take each piece of our monomial term inside the parentheses of 2a

^{2}b

^{3}c

^{4} - 6x

^{3}y

^{4}z

^{5}, and raise it to a power of 5

__Piece 1__2

^{5} = 2 x 2 x 2 x 2 x 2 = 32

__Piece 2__(a

^{2})

^{5} = a

^{(2 x 5)} = a

^{10}__Piece 3__(b

^{3})

^{5} = b

^{(3 x 5)} = b

^{15}__Piece 4__(c

^{4-6})

^{5} = c

^{(4-6 x 5)} = c

^{20}__Piece 5__(x

^{3})

^{5} = x

^{(3 x 5)} = x

^{15}__Piece 6__(y

^{4})

^{5} = y

^{(4 x 5)} = y

^{20}__Piece 7__(z

^{5})

^{5} = z

^{(5 x 5)} = z

^{25}__Piece together our answer:__(2a

^{2}b

^{3}c

^{4} - 6x

^{3}y

^{4}z

^{5})

^{5} =

**32a**^{10}b^{15}c^{20}x^{15}y^{20}z^{25}